The Practice of Judo as a Modulation of Self-Concept, Self-Esteem and School Performance of Students of First Cycle of Primary School - da Silva Batista, Marco Alexandre (2012)
This study aimed at relating the general practice of judo to the development of self-concept, self-esteem, and school performance in children of the first cycle of primary school education. We worked with a sample of 531 Portuguese students, with an age mean of 9.13 years old, ranging from a minimum of 8 and a maximum of 10 years old. Out of this sample, 394 students (74%) do at least one formal extracurricular physical activity, and 96 students (24%) practice judo with an experience ranging between 9 months and five years. As an instrument for data collection, we used the Scale of Self-concept by Susan Harter validated for Portuguese population (Martins, Peixoto, Mata, & Monteiro, 1995). Also, school performances have been recorded. Discussion groups with judo coaches and parents were held in order to find out opinions and arguments about the practice of judo and its importance and connection to self-concept, self-esteem, and school performance. Apparently, the results show that students' practice of judo promotes a significant evolution in the development of self-concept and academic achievement, and also they suggest an evolutionary trend in positive self-esteem in students who practice judo.